2D Resistivity Tomography of Doly Rostey Proposed Small Dam Site, Soran Subdistrict, NE of Erbil City-Iraqi Kurdistan Region: resistivity survey - Bakhtiar Qader Aziz; Ghaib, Fadhil Ali (Zanco Journal of Pure and Applied Sciences, 2025)
The present study investigates the subsurface conditions for a proposed small dam in Doly Rostey, situated in the extreme northeastern part of Erbil City within the Iraqi Kurdistan Region. To achieve this, four profiles were surveyed: one along the dam axis (NW-SE direction), two along the abutments, and one along the stream parallel to the abutments (NE-SW direction). Each profile spanned 355 meters, employing a Wenner-Schlumberger electrode configuration with 5-meter electrode spacing. Field data were processed and interpreted using the software “RES2DINV” (version 3.59.117), generating four detailed 2D resistivity inversion sections. The results revealed the Qamchuqa Formation as the dominant subsurface feature, with resistivity values of 500 to 60,000 Ω·m, indicative of dolomitic and limestone layers. The study also identified karstic features, fractured zones, and potential faults, highlighting structural complexity and pathways for water movement. Additionally, low-resistivity zones (45–500 Ω·m), corresponding to surface sediments and marly limestone within the uppermost 16–60 meters. These findings emphasize the site’s structural and lithological variability and highlight the critical need for detailed geotechnical and hydrological evaluations to ensure the dam's stability and safety.